Antimicrobial Effect of Polymer-Based Silver Nanoparticle Coated Pedicle Screws: Experimental Research on Biofilm Inhibition in Rabbits - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Study Design.Antimicrobial effect of a novel silver-impregnated pedicle screw in rabbits.Objective.A novel spine implant model was designed to study the antimicrobial effect of a modified Titanium (Ti) pedicle screws with methicillin-resistant Staphylococcus aureus (MRSA) in multiple surgical sites in the lumbar spine of a rabbit.Summary of Background Data.Infection in spinal implant is of great concern. Anti-infection strategies must be tested in relevant animal models that will lead to appropriate clinical studies.Methods.Fourteen New Zealand white rabbits were divided into 2 groups: group 1: infected unmodified Ti screw group (n=6), and group 2: infected polyethylene glycol grafted, polypropylene-based silver nanoparticle (PP-g-PEG-Ag) covered Ti screw group (n=6), and 2 rabbits as sterile (sham-operated and control) group. In all groups, left L4-right L6 vertebra levels were exposed and screws were drilled to transverse processes after contamination of burr holes and surrounding tissue with 0.1mL of 10(6) colony forming units (CFU) MRSA solutions in groups 1 and 2. After 21 days, samples were collected and infection was analyzed via light and scanning electron microscopy and culturing. Silver nanoparticles (Ag-NP) on the screws and tissues were assayed pre and postoperatively.Results.The bacterial colony count for modified-Ti screw group was lower than for unmodified Ti screw (17.2 versus 200x10(3)CFU/mL, P=0.029) with less biofilm formation. There was no difference in duration of surgery among groups and within the surgical sites. Ag-NPs were detected on the screw surface postoperatively.Conclusion.This novel experimental design of implantation in rabbits is easy to apply and resembles human stabilization technique. Modified Ti screws were shown to have antimicrobial effect especially inhibiting the biofilm formation. This anchored Ag NPs that remained after 21st day of implantation shows that it is resistant to tapping forces of the screw.Level of Evidence: N/A
Keywords: Ag nanoparticles; antimicrobial; biofilm; infection; polyethylene glycol; polypropylene; rabbit; spine; spine implant model; VENTRICULAR CATHETERS; STAPHYLOCOCCUS-AUREUS; IN-VIVO; INFECTION; PREVENTION; EFFICACY; FUSION